Management and Outcomes of Childhood Renal Artery Stenosis and Middle Aortic Syndrome. (24th January 2018) - Rumman, Rawan K; Matsuda-Abedini, Mina; Langlois, Valerie; Radhakrishnan, Seetha; Lorenzo, Armando J; Amaral, Joao; Mertens, Luc; Parekh, Rulan S
Abstract: BACKGROUND: Renal artery stenosis (RAS) in isolation or in conjunction with middle aortic syndrome (MAS) are important vascular causes of childhood hypertension. Few longitudinal studies have assessed the risk of surgical or endovascular intervention, and outcomes by etiology or extent of vascular disease. METHODS: In a retrospective study of 93 children seen over 30 years with RAS and/or MAS, data on vascular involvement (isolated RAS vs. RAS with MAS), etiology (unknown, inflammatory, or genetic), and management were collected. Time to first intervention (endovascular or surgical) was assessed by Cox regression. Mixed-effects analysis examined the longitudinal change in blood pressure after intervention compared to antihypertensive medications alone. RESULTS: Children were 7.0 ± 5.4 years old. Etiology was unknown in 50%, genetic in 26% and inflammatory in 24% of children. Children had isolated RAS (49%) or MAS with or without RAS (51%). Overall, 70% were managed with surgical or endovascular intervention. After adjusting for age, sex, and systolic blood pressure, children with unknown etiology had a higher risk of intervention compared to those with genetic and inflammatory diseases (hazard ratio 3.1, 95% confidence interval [CI] 1.7, 5.6). Children with RAS and MAS were less likely to receive intervention (hazard ratio 0.4, 95% CI 0.2, 0.8) than isolated RAS. Over a median follow-up of 2 years, 65% remained hypertensive. The longitudinal changes in systolic blood pressure did not differ by etiology, or between interventional and medical management. CONCLUSIONS: Hypertension persists despite endovascular or surgical management of childhood RAS and MAS highlighting the importance of close monitoring and ongoing medical management.